Benjamin’s Dialectical Image and the Textuality of the Built Landscape - Ross Lipton (Footprint)
In The Arcades Project, Walter Benjamin describes the architectural expression of nineteenth century Paris as a dialectical manifestation of backwards-looking historicism and the dawn of modern industrial production (in the form of cast iron and mass produced plate glass). Yet in the same text, Benjamin refers to the dialectical image as occurring within the medium of written language. In this paper, I will first discuss the textuality of the dialectical image as it emerges from Benjamin’s discussion of allegorical and symbolic images in his Trauerspiel study and the ‘wish symbol’ in The Arcades Project. I will then discuss the ‘textual reductionism’ implicit in Benjamin’s theory of the dialectical image, in which the dense pluralities of urban space are reduced to a finite script to be pieced together through Benjamin’s constructivist method of historical observation. The textuality of the dialectical image will be elaborated on by discussing it in relation to the practice of translation. This discussion will be further contextualised by discussing a cadre of German/Austrian planners and architects who attempted to translate architectural idioms between cultural identities in Kemalist Era Turkey. The article concludes with a short recapitulation on the dialectical image as both an object of scrutiny and a method of observation, one which also takes into consideration the specific historicity of the observer.